(f – g)(x) = 7x - √2 - (x + √2)
(f – g)(x) = 7x - √2 - x - √2
<span>(f – g)(x) = 6x - 2</span>√2
The answer is C because when you rotate 90 degrees clockwise (x,y) becomes (y,-x)
Answer:
Firstly, notice the relationship the two triangles have. They have conjoining ends that form vertical angles (looks like a middle x). Vertical angles are equivalent in measure of degrees.
Secondly, notice that the triangle on the right side is a right triangle. One of its angle's measurements are also given; 40 degrees. If you know that the sum of a triangle's angles equal 180 degrees, then simply subtract the known angles measurements from 180.
180-(90+40)= 180-130=50.
Therefore, the vertical angles measurement is equivalent to 50 degrees.
Apply the principle of the sum of all angles in a triangle equivalent to 180 degrees to the left triangle, and you will be able to find the measurement of the "?" angle.
180-(50+25)= 180-75=105
SO HERE IS YOUR ANSWER= 105 degrees is the value of the angle marked with a "?"
I hope you are having a great day too;)!
Step-by-step explanation:
![\lim_{n \to \infty} \sum\limits_{k=1}^{n}f(x_{k}) \Delta x = \int\limits^a_b {f(x)} \, dx \\where\ \Delta x = \frac{b-a}{n} \ and\ x_{k}=a+\Delta x \times k](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%5Csum%5Climits_%7Bk%3D1%7D%5E%7Bn%7Df%28x_%7Bk%7D%29%20%5CDelta%20x%20%3D%20%5Cint%5Climits%5Ea_b%20%7Bf%28x%29%7D%20%5C%2C%20dx%20%5C%5Cwhere%5C%20%5CDelta%20x%20%3D%20%5Cfrac%7Bb-a%7D%7Bn%7D%20%5C%20and%5C%20x_%7Bk%7D%3Da%2B%5CDelta%20x%20%5Ctimes%20k)
In this case we have:
Δx = 3/n
b − a = 3
a = 1
b = 4
So the integral is:
∫₁⁴ √x dx
To evaluate the integral, we write the radical as an exponent.
∫₁⁴ x^½ dx
= ⅔ x^³/₂ + C |₁⁴
= (⅔ 4^³/₂ + C) − (⅔ 1^³/₂ + C)
= ⅔ (8) + C − ⅔ − C
= 14/3
If ∫₁⁴ f(x) dx = e⁴ − e, then:
∫₁⁴ (2f(x) − 1) dx
= 2 ∫₁⁴ f(x) dx − ∫₁⁴ dx
= 2 (e⁴ − e) − (x + C) |₁⁴
= 2e⁴ − 2e − 3
∫ sec²(x/k) dx
k ∫ 1/k sec²(x/k) dx
k tan(x/k) + C
Evaluating between x=0 and x=π/2:
k tan(π/(2k)) + C − (k tan(0) + C)
k tan(π/(2k))
Setting this equal to k:
k tan(π/(2k)) = k
tan(π/(2k)) = 1
π/(2k) = π/4
1/(2k) = 1/4
2k = 4
k = 2
All good and for number 6 you should draw an acute angle